PERAN INOVASI DAN PENGUATAN DAYA SAING BISNIS DENGAN PENERAPAN LEAN SIX-SIGMA CONCEPT - Supriyanto, Hari (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
ABSTRACTThe dynamics and development of the global economy can give a positive signal to the importance of improvement on empowerment and product competitiveness in the market. It takes well thought plan to build competitive advantage, which is the basis for increasing production and business competitiveness. Increasing production is a series of activities to shape productivity. If one production activity experiences failure, it will affect the quality and production capacity. Failure is usually indicated by waste / excess that appears along the value stream. There is a high indication of defect exceeding 10% in sorting and packaging process. The main problem is the presence of waste / excess which results in a decrease in quality and production capacity. This paper will identify the waste that occurs in the production process, look for the root causes of the waste, and build alternative remedial solutions. Creative thinking is required to increase resource efficiency and business competitiveness in the market. The method used to solve the problem is Lean six-sigma. This concept traces the problem of inefficiency by finding nonvalue added activity from the emergence of waste along the value stream. The emergence of waste is further identified with root cause analisys (RCA) and failure mode and effects analysis (FMEA). The end result of FMEA is the risk priority number (RPN) which describes the priority over the risk mode for remedial. From the priority results, 3 improvement alternatives are designed, namely operator training, the making of SOP of production process, and quality control employee training. With the net present value (NPV) approach, a positive NPV value is obtained, meaning that the alternative is feasible to run. This alternative increases the sigma value from the initial sigma of 2.80 to 3.30. An increase in sigma value will indicate a decrease in the level of defect per million opportunities (DPMO), and resulting in a decrease in costs up to 20%. Keywords: Competitiveness, Competitive Advantage, Lean Six Sigma, RCA, FMEA, DPMOABSTRAKDinamika dan perkembangan ekonomi global dapat memberikan sinyal positif terhadap pentingnya peningkatan pemberdayaan dan daya saing produk di pasar. Dibutuhkan pemikiran untuk membangun keunggulan kompetitif, yang menjadi dasar bagi peningkatan produksi dan daya saing bisnis. Peningkatan produksi merupakan serangkaian aktifitas untuk membentuk produktifitas. Bila salah satu aktifitas produksi mengalami kegagalam maka akan berpengaruh pada kualitas dan kapasitas produksi. Kegagalan biasanya terindikasi dari waste/ pemborosan yang muncul di sepanjang value stream. Terdapat indikasi defect yang tinggi melebihi 10% di sortir dan packaging process. Permasalahan utama adalah adanya waste/ pemborosan yang mengakibatkan penurunan kualitas dan kapasitas produksi. Paper ini akan mengidentifikasi waste yang terjadi di proses produksi, mencari akar penyebab terjadinya waste, dan membangun alternatif solusi perbaikan.  Diperlukan pemikiran kreatif untuk dapat menaikkan efisiensi sumber daya dan daya saing bisnis di pasar. Metoda yang dipakai untuk menyelesaikan permasalahan adalah Lean six-sigma. Konsep ini menelusuri permasalahan inefisiensi dengan cara mencari nonvalue added activity dari munculnya waste di sepanjang value stream.  Kemunculan waste selanjutnya diidentifikasi lebih dalam dengan root cause analisys (RCA) dan failure mode and effects analysis (FMEA). Hasil akhir dari FMEA adalah risk priority number (RPN) yang menggambarkan prioritas atas mode resiko untuk dilakukan perbaikan. Dari hasil prioritas dirancang 3 alternatif perbaikan yaitu pelatihan operator, pembuatan SOP proses produksi, dan pelatihan karyawan quality control.   Dengan pendekatan net present value (NPV), maka diperoleh nilai NPV yang positif, artinya alternatif tersebut adalah layak untuk dijalankan. Alternatif ini meningkatkan nilai sigma dari sigma awal sebesar 2,80 menjadi 3,30. Kenaikan nilai sigma akan memberi indikasi adanya penurunan tingkat defect per million opportunities (DPMO), dan berakibat pada penurunan biaya sampai 20%.  Kata kunci: daya saing, keunggulan kompetitif, Lean Six Sigma, RCA, FMEA, DPMO